The Influence Of Sociodemographic Factors On The Success Of Exclusive Breastfeeding: A Narrative Review - Qomariah Dianti Sari (Jurnal EduHealth, 2024)
Exclusive breastfeeding is the best primary food for infants and lasts for 6 months. However, the practice of exclusive breastfeeding is often influenced by social, economic, and environmental factors, resulting in poor practices. This study aims to analyze the influence of sociodemographic factors on the success of exclusive breastfeeding. The research method used in this study is a literature review with the type is narrative review. The article search process in this study used the keywords "Socio-demographic factor" OR "Demographic influence" OR "Socio-demographic impact" OR "Influence socio-demographic factor" AND "Exclusive Breastfeeding" OR "Successful Breastfeeding" OR "Breastfeeding Practice" in the PubMed, ScienceDirect, Web of Science, Taylor & Francis and DOAJ databases. Inclusion criteria in this study were articles in full text, English language not in the form of literature review, systematic review or meta-analysis, and articles outside the 2019-2024 range and grey literature were excluded. The article synthesis process was carried out using the Prisma Flow Diagram. There are several factors that influence the practice of exclusive breastfeeding including maternal occupation, maternal education, socioeconomic status, ANC, infant age at breastfeeding, caesarean section, early initiation of breastfeeding, maternal age, residence, parity, education on the importance of exclusive breastfeeding, infant weight, infant gender, maternal attitude and efficacy level, and smoking status. The most significant sociodemographic factors influencing exclusive breastfeeding practices were maternal occupation, maternal education, and family socioeconomic status.